2011
DOI: 10.5402/2011/416435
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic and Nonneoplastic Cutaneous Tumors of Dogs in Grenada, West Indies

Abstract: This retrospective survey was undertaken between 2002 and 2007 on samples from dogs residing in Grenada. The objectives of the study were to identify the most common histologic types of canine cutaneous tumors, determine the relative frequency of each tumor type, and compare results to reports from other regions. In a series of 225 skin masses examined, the proportion of neoplasms was 72% whereas nonneoplastic tumors accounted for 15.6%, and inflammatory conditions constituted 12.4%. There were 10 types of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 15 publications
(22 reference statements)
1
36
3
3
Order By: Relevance
“…Interestingly, in geographical regions with higher levels of solar radiation than Korea, such as Zimbabwe and Grenada, common tumor types differed markedly. In Zimbabwe, squamous cell carcinoma accounted for the most, while in Trinidad, Grenada, and South Africa, hemangiosarcoma comprised the high proportion of canine skin tumor types (Mukaratirwa et al, 2005;Chikweto et al, 2011;Suepaul et al, 2019;Tompkins et al, 2019). This may reflect the inductive effect of ultraviolet radiation on hemangiosarcoma or squamous cell carcinoma, as suggested in previous studies (Nikula et al, 1992;Pirie et al, 2006;Kim and He, 2014), and furthermore, natural environments could be influencing factors for canine tumor etiology.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, in geographical regions with higher levels of solar radiation than Korea, such as Zimbabwe and Grenada, common tumor types differed markedly. In Zimbabwe, squamous cell carcinoma accounted for the most, while in Trinidad, Grenada, and South Africa, hemangiosarcoma comprised the high proportion of canine skin tumor types (Mukaratirwa et al, 2005;Chikweto et al, 2011;Suepaul et al, 2019;Tompkins et al, 2019). This may reflect the inductive effect of ultraviolet radiation on hemangiosarcoma or squamous cell carcinoma, as suggested in previous studies (Nikula et al, 1992;Pirie et al, 2006;Kim and He, 2014), and furthermore, natural environments could be influencing factors for canine tumor etiology.…”
Section: Discussionmentioning
confidence: 56%
“…Os hamartomas são considerados lesões nodulares não neoplásicas e primariamente não inflamatórias (MILLER et al, 2013). De acordo com um estudo feito por Chikweto et al (2011), em Granada, na América Central, o hamartoma se apresentou como a forma mais comum de lesão não neoplásica em cães (28,5%), contudo outros autores consideram seu aparecimento raro (GROSS et al, 2005;GOLDSCHIMIDT;GOLDSCHIMIDT, 2017).…”
Section: Discussionunclassified
“…Diversos autores discutem acerca da possível etio-logia para o processo, atribuindo-a à alterações congênitas ou mesmo a reações inflamatórias crônicas, além da participação de outros fatores como a própria predisposição racial e idade (GROSS; IHRKE; WALDER, 1992; GOLDSCHMI-DT; SHOFER, 1992;EL-DAROUTY et al, 2001;GROSS et al, 2005;BOYLE;HILL, 2014;MAXIE et al, 2016). Entretanto, pouco ainda se conhece sobre a verdadeira relevância de fatores como sexo, raça e idade no aparecimento dos hamartomas, ou ainda se, na verdade, outros elementos possam estar diretamente associados a sua origem, como o clima e exposição solar (CHIKWETO et al, 2011), ou mesmo o padrão de tamanho do pelo, pois, conforme estudado por Gross et al (1992), acredita-se que cães de pelo longo possuam maior predisposição para o desenvolvimento de neoplasias foliculares, posto que nesses animais a fase de crescimento piloso anagênica esteja em constante ocorrência. Contudo, no presente caso, o padrão de cobertura pilosa do animal em questão se constituía por ser do tipo curto.…”
Section: Discussionunclassified
“…Based on the survey on dermatological conditions of dogs conducted by Hill et al (2006) in UK, cutaneous parasitic infestations, bacterial infections and neoplasia were noticed in majority of the cases. Of all the cutaneous neoplasms of dogs, tumours of vascular origin and transmissible venereal tumours were considered as more common one (Chikweto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that, breed and ultraviolet radiation are the major risk factors for various canine cutaneous hemangiomas, hemangiosarcomas and squamous cell carcinomas (Hargis et al, 1992;Nikula et al, 1992;Chikweto et al, 2011). Spontaneous tumours of blood vessel endothelial cells were described commonly in the dog, less frequently in the cat and horse, and sporadically in most other domestic species (Goldschmidt &Hendrick, 2002).…”
Section: Introductionmentioning
confidence: 99%